2022
DOI: 10.1097/yco.0000000000000806
|View full text |Cite
|
Sign up to set email alerts
|

The physical and mental health consequences of social isolation and loneliness in the context of COVID-19

Abstract: Purpose of reviewSocial isolation and loneliness are known contributors to all-cause mortality as well as a range of physical and mental health conditions. Therefore, this article reviews current literature pertaining to the effects of social isolation and loneliness on physical and mental health during the current COVID-19 pandemic. Recent findingsSocial isolation and loneliness contribute to a myriad of physical and mental health conditions. Specifically social isolation and loneliness contribute to the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…In addition to the possible direct effect of SARS-CoV-2 infection on the development of dementia, previous studies suggested that social isolation and loneliness are related to cognitive decline and the risk of future dementia [ 137 ]. In particular, a recent study by Shen and colleagues utilizing a UK-Biobank cohort of 462,619 participants with a mean follow-up period of 11.7 years indicated that social isolation is associated with a 1.26-fold increase of risk of developing dementia, which is independent of loneliness and other risk factors [ 138 ].…”
Section: Covid-19 and Admentioning
confidence: 99%
“…In addition to the possible direct effect of SARS-CoV-2 infection on the development of dementia, previous studies suggested that social isolation and loneliness are related to cognitive decline and the risk of future dementia [ 137 ]. In particular, a recent study by Shen and colleagues utilizing a UK-Biobank cohort of 462,619 participants with a mean follow-up period of 11.7 years indicated that social isolation is associated with a 1.26-fold increase of risk of developing dementia, which is independent of loneliness and other risk factors [ 138 ].…”
Section: Covid-19 and Admentioning
confidence: 99%
“…13 Such phenomenon reinforced the association of social isolation and loneliness with eating disorders, particularly overeating and binge eating as a coping mechanism, contributing to weight gain and obesity via excess caloric balance. 5,19,20…”
Section: Impact Of Covid-19 Pandemic On Eating Behaviorsmentioning
confidence: 99%
“…The result of a negative psychological impact could be permanent and fuels additional undesirable physical health outcomes long-term. 5,43…”
Section: Impacts Of Covid-19 Pandemic Lockdown On Adolescents' Mental...mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that social isolation and loneliness have significant consequences on the physical and mental health and that the move towards ending all lock-down and social distancing measures against COVID-19 has important significant implications for the vulnerable. Furthermore, the similarities between the effects of social isolation and loneliness are compared to some of the conditions evident in long-COVID [1].…”
mentioning
confidence: 99%